ASSET AND LIABILITY MANAGEMENT: A MULTIPLE CASE STUDY IN BRAZILIAN FINANCIAL INSTITUTIONS - Trasmontano, Priscila da Silva; Neto, Julio Vieira (Brazilian Journal of Operations & Production Management, 2016)
In the face of an unstable scenario, many banks began to implement the Asset and Liability Management – ALM, in order to mitigate possible risks, and maximize profitability. In view of this, this study proposes the following problem situation: which managerial resources promote the implementation of ALM and avoid future problems within Brazilian financial institutions? Our objective is to investigate how Brazilian financial institutions are structuring the ALM. The methodological resource adopted was a Multiple Case Study with qualitative exploratory research based on a perception survey from Brazilian market specialists that deal with ALM in banks and pension funds. Among the data collected for implementation, the most prominent were: the identification of assets in which the institution can potentially invest, point estimates of the return on these assets, pertinent legal constraints, parameters used in the development of liquidity constraints and policy constraints adopted by the institution.